'Blank figures' and the material organisation of knowledge: experiences of a 'project file'. (21st April 2011) - Sage, Dan; Dainty, Andy; Brookes, Naomi
In this paper, we seek to develop an understanding of the material organisation of knowledge through the milieu of a construction project and the artefact of a 'project file'. We draw upon two concepts developed within science and technology studies (STS) to try and account for its life: 1) mutable mobiles; 2) boundary objects. An element of the power and potential of the project file can be captured by each of these concepts, yet each is shown here to be insufficient to fully articulate the multiple organisational realities that the project file helps act out. This leads us to conclude that this object might be better understood through the concept of the 'blank figure': an object whose autonomous under-determined material form is crucial to the performance of broader processes of organisational stasis and change, as well as knowledge of similarity and difference.